Hauntology and spectres of personal trauma in Ruskin Bond’s “Topaz” and “The Woman on Platform No. 8” - Priyank Jain,; Anita Harris Satkunananthan, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The article deploys Jacques Derrida’s hauntological contextualising of spectres in tandem with Dominick LaCapra’s (2004) and E. Ann Kaplan’s (2005) contextualising of trauma to unearth the roles which women are made to play within the societies in Ruskin Bond's narratives. Utilising a hauntological treatment of trauma, two short stories by Bond, “Topaz” and “The Woman on Platform No. 8,” will be analysed in this article. In particular, this article aims to interrogate the impact of personal trauma contained within the texts as experienced by the women spectres inhabiting both of the aforementioned short stories and their male interlocutors. An analysis of both texts from a hauntological perspective incorporates both spatial and temporal considerations, from the architecture of the enfolding spaces to the connection between past, present and future. The different environments determined the different forms taken by spectres within Ruskin’s texts take; therefore, their significance will be examined in this article. In so doing, the article will problematise the notion of revisiting and re-contextualise it from a hauntological perspective. The findings will unearth the ways in which the feminine spectres in these tales are equated with the spaces they inhabit, both in nature and in the ties to architecture.